Security and diplomacy amid uncertainties - Zarina Othman,; Bakri Mat,; Muhammad Danial Azman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Volume 4, Issue 2, 2024 edition of the SINERGI: Journal of Strategic Studies & International Affairs examines key themes in history, diplomacy and security, with a strong focus on China’s role in shaping global and regional dynamics. From its historical connections with Islam during the Tang Dynasty to its modern Belt and Road Initiatives in Southeast Asia, China’s influence remains pivotal. Articles explore China’s impact on Indonesia’s foreign policy, Malaysia’s migrant labour governance, and Taiwan’s technological aspirations. Broader topics, including the US presidential election, Gulf States’ responses to the Palestine-Israel conflict, and Myanmar’s instability, are also addressed. This edition further highlights Malaysia’s developmental policies, its ties with China, and critical book reviews on regional strategies. Together, the articles offer diverse perspectives on historical legacies and modern political challenges, providing valuable insights into international diplomacy and the complexities of a multipolar world.